Self-directed teaching: a holistic framework for educator autonomy - Mohiyeddini, Changiz (Frontiers in Medicine, 2024)
Over recent decades, the complexity of higher education in general, and teaching specifically, has increased significantly, resulting in a myriad of challenges for educators. Traditional approaches to teaching often rely on standardized curricula and top-down instructional methods. Therefore, they are critically scrutinized for their lack of adaptability and limitations in addressing the diverse needs of contemporary educators and learners. The purpose of this paper is to introduce the concept of self-directed teaching (SDT) as a response to the contemporary challenges in education and explore its relevance and potential impact on educators and learners. SDT is proposed as a holistic, theory-based, proactive approach that integrates multiple core aspects of the teaching process into a cohesive framework. It aims to empower educators to embrace their autonomy, control their professional development, and adapt their teaching strategies, much like the concept of self-directed learning (SDL) applies to students. SDT has the potential to promote educator autonomy, provide strategies to address burnout, and offer adaptable approaches to meet diverse educational contexts. It encourages educators to tailor their teaching strategies and engage in continuous professional development, positioning them to respond flexibly to changing educational demands. Furthermore, this article outlines the theoretical foundations of SDT, grounded in theories such as self-directed learning, self-determination theory, and constructivist theory. Key components of SDT including autonomy awareness, teaching needs diagnosis, goal setting, resource identification, and continuous evaluation and reflection are discussed including strategies for successful implementation of SDT.